THE ANALYSIS OF THE PHYSICAL PROPERTIES OF SPECIAL FABRICS (Conferencea, 2022)
Strong and durable clothes are necessary for many areas of human activity - at work, in service and at leisure. Such textiles are made of special rip-stop fabrics. The purpose of the work: design of the fabric for tear resistance, determination of initial technological factors and production of this fabric.